2020
DOI: 10.21203/rs.3.rs-37040/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Shirom-Melamed Vigor Measure for students and how vigor relates to academic performance, mental health and satisfaction with life: Factorial analysis and construct validity in Spanish undergraduate university students

Abstract: Background Students suffer from a decrease in physical activity during their education period. This lower level of activity could affect, through various paths, their academic performance, mental health and satisfaction with life. In this study, we assume that vigor, a positive affect variable, would act as a mediating variable in the above relationship, and thus, we propose an instrument for evaluating vigor in academic contexts. To attain this aim, the factorial validity and reliability of the proposed vigo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…In this study we used the adaptation to Spanish by Notario-Pacheco et al (Notario-Pacheco et al, 2011). In terms of psychometric properties, it has good internal consistency (alpha = .87) (Soler, Meseguer, & García, 2016) and measurement invariability in terms of sex and age, and is suitable for measuring resilience in the general Spanish population (Pulido-Martos, Cortés-Denia, Rosa-Blanca, & López-Zafra, 2020). In this study we found an alpha of .88.…”
Section: Instrumentsmentioning
confidence: 76%
“…In this study we used the adaptation to Spanish by Notario-Pacheco et al (Notario-Pacheco et al, 2011). In terms of psychometric properties, it has good internal consistency (alpha = .87) (Soler, Meseguer, & García, 2016) and measurement invariability in terms of sex and age, and is suitable for measuring resilience in the general Spanish population (Pulido-Martos, Cortés-Denia, Rosa-Blanca, & López-Zafra, 2020). In this study we found an alpha of .88.…”
Section: Instrumentsmentioning
confidence: 76%